MoO2/C composites prepared by tartaric acid and glucose-assisted sol-gel processes as anode materials for lithium-ion batteries - Zakharova, Galina S.; Singer, Lennart; Fattakhova, Z. A.; Wegener, Simon; Thauer, Elisa; Zhu, Q.; Shalaeva, E. V.; Klingeler, Rüdiger (Journal of alloys and compounds, 2021)
MoO2/C-composites have been fabricated for the first time by a tartaric acid/glucose-assisted sol-gel method with post-annealing at 500 °C for 1 h in N2 flow. The synthesized materials were fully characterized with respect to structure, morphology, and electrochemical properties. Compared with tartaric acid-assisted products, the adoption of glucose as carbon source effectively increases the carbon content in the composites. Irrespective of the organic component, the composites exhibit low crystallinity and small grain size. This results in good electrochemical performance of the anode materials as confirmed for the glucose-assisted materials which after additional post treatment delivers a competitive electrochemical capacity.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 22.07.2021